2009
DOI: 10.1152/ajpregu.00087.2008
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin has acute and chronic effects on the cerebral circulation of fetal sheep

Abstract: We studied the impact of endotoxemia on cerebral blood flow (CBF), cerebral vascular resistance (CVR), and cerebral oxygen transport (O(2) transport) in fetal sheep. We hypothesized that endotoxemia impairs CBF regulation and O(2) transport, exposing the brain to hypoxic-ischemic injury. Responses to lipopolysaccharide (LPS; 1 microg/kg iv on 3 consecutive days, n = 9) or normal saline (n = 5) were studied. Of LPS-treated fetuses, five survived and four died; in surviving fetuses, transient cerebral vasoconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
37
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 73 publications
15
37
3
1
Order By: Relevance
“…Carotid vascular conductance was significantly increased in LPS-treated animals before occlusion consistent with our previous report (22) and previous studies that found increased carotid blood flow despite hypotension (10,25). Despite this marked central vasodilation, occlusion was associated with a rapid reduction in conductance that was not significantly different to saline-treated fetuses.…”
Section: R801supporting
confidence: 91%
See 1 more Smart Citation
“…Carotid vascular conductance was significantly increased in LPS-treated animals before occlusion consistent with our previous report (22) and previous studies that found increased carotid blood flow despite hypotension (10,25). Despite this marked central vasodilation, occlusion was associated with a rapid reduction in conductance that was not significantly different to saline-treated fetuses.…”
Section: R801supporting
confidence: 91%
“…These data are difficult to interpret given that high-dose LPS by itself is associated with severe hypotension and a high risk of death over 4 to 7 h (7,8,10,22,25). Supporting a direct effect, there is evidence of impaired chemoreflex responses in adult patients with sepsis and multiple organ failure (29,30) and after acute LPS injection in anesthetized adult cats and neonatal piglets (11,23).…”
mentioning
confidence: 99%
“…Multiple studies have shown that fetal sheep exposed to acute boluses of Gram-negative LPS commonly develop white matter damage [63,64,65,66,67,68,69,70,71]. Typically, such large doses are associated with acute loss of a third to over 40% of fetuses associated with terminal hypotension [64,67,72], similar to the deaths of 6/11 fetuses in a recent report [73]. …”
Section: Prenatal Infection/inflammation In Sheepmentioning
confidence: 76%
“…23,24 In addition, proinflammatory cytokines may affect the central nervous system by increasing the permeability of the developing blood brain barrier exclusively observed in the cerebral white matter, 25 and by impairing the cerebral blood flow. 26 Second, developing oligodendrocytes are injured by reactive oxygen species and reactive nitrogen species generated by either oligodendrocyte glutamatergic excitotoxicity or microglial activation. The activated microglia generate free radicals and induce the ultimate death of the antioxidant-deficient immature oligodendrocytes.…”
Section: Multiorgan Overviewmentioning
confidence: 99%